Short-Term Plasticity at Olfactory Cortex to Granule Cell Synapses Requires CaV2.1 Activation - Zhou, Fu-Wen; Puche, Adam C.; Shipley, Michael T. (Frontiers in Cellular Neuroscience, 2018)
Output projections of the olfactory bulb (OB) to the piriform cortex (PC) and reciprocal feedback projections from PC provide rapid regulation of OB circuit dynamics and odor processing. Short-term synaptic plasticity (STP), a feature of many synaptic connections in the brain, can modulate the strength of feedback based on preceding network activity. We used light-gated cation channel channelrhodopsin-2 (ChR2) to investigate plasticity of excitatory synaptic currents evoked at the PC to granule cell (GC) synapse in the olfactory bulb. Selective activation of PC glutamatergic axons/terminals in OB generates strong, frequency-dependent short-term plasticity in GCs. This plasticity was critically dependent on activation of Cav2.1 channels. As ACh modulates Cav2.1 channels in other brain regions and as cholinergic projections from the basal forebrain heavily target the granule cell layer in OB, we investigated whether ACh modulates STP at the PCGC synapse. ACh decreases PCGC evoked EPSCs, it had no effect on STP. Thus, ACh impact on cortical feedback is independent of Cav2.1-mediated STP. Modulation of PC feedback to the bulb by modulatory transmitters, such as ACh, or by frequency-dependent STP could regulate the precise balance of excitation and inhibition of GCs. As GCs are a major inhibitory source for OB output neurons, plasticity at the cortical feedback synapse can differentially impact OB output to higher-order networks in situations where ACh inputs are activated or by active sniff sampling of odors.